HUBUNGAN PENGETAHUAN DAN SIKAP IBU MENYUSUI TENTANG BENDUNGAN ASI DI PMB Hj. MARIANI KOTA MAKASSAR TAHUN 2021 - Junaeda Rasyad; Hadijah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Breastfeeding is one of the best for babies because by breastfeeding the baby's nutritional needs will be met, at the age of more than 25 years, a third of women in the world (38%) agree not to breastfeed their babies (IDHS, 2012). Breastfeeding is an unrivaled way of providing ideal food for the healthy growth and development of babies. In addition, it has a unique biological and psychological effect on the health of mothers and babies. Anti-infective substances contained in breast milk help protect the baby against disease. However, breastfeeding is not always able to run normally, not a few mothers complain such as breast swelling due to the accumulation of breast milk, because the milk is not expelled or sucked by the baby (Heryani, 2012). The purpose of this study was to determine the relationship. To determine the relationship between knowledge and attitudes of breastfeeding mothers about ASI dams at PBM Hj. Mariani Makassar City. This type of research is an analytic survey with a cross sectional study approach. population and sample were all postpartum mothers from December 2021 to February 2022 (13 people) with accidental sampling technique which was then analyzed using chi-square. The results showed that there was no significant relationship between mother's knowledge and attitudes towards breastfeeding dams. It is hoped that breastfeeding mothers and families will be active in finding out about ways to prevent breast milk dams